Perbandingan Aktivitas Fisik dan Kebugaran Jasmani Antara Siswi Madrasah Aliyah Matholi’ul Huda Bugel Kedung Jepara yang Tinggal di Pondok Pesantren dan Non Pondok Pesantren - Dintuqatih, Nisavinea; Rahayu, Setya; Irawan, Fajar Awang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to compare physical activity and physical fitness between Madrasah Aliyah Matholi'ul Huda Bugel Kedung Jepara students who live in Islamic boarding schools and those who do not live in Islamic boarding schools. This type of research is quantitative with a survey design. The research subjects used in this research were all MA Matholi'ul Huda Bugel Kedung Jepara students. The sampling technique uses total sampling. Data collection by observation, questionnaires, tests and documentation. Quantitative data analysis consisted of normality tests, hypothesis testing using SPSS version 26 software. The results showed that MA Matholi'ul Huda Bugel Kedung Jepara students had a moderate physical activity level of 462 (64%). The level of physical activity was high at 263 (64%). The overall physical activity level of female students is in the medium category. MA Matholi'ul Huda Bugel Kedung Jepara female students had a very good physical fitness level of 52 (7%). The good category was 315 (43%). The sufficient category was 72 (10%). The physical fitness level of all female students is in the good category. The Cottage Physical Activity Value = 389.07 is higher than the Non-Cottage group = 347.71. The Physical Fitness Score of the Non-Pottage TKPN = 378.53 is higher than that of the Pondok Group which is = 336.51.